Clinicopathological study of radicular cysts with actinomycosis - Ming-Jay Hwang; Yi-Pang Lee; Ming-Jane Lang; Yu-Hsueh Wu; Chun-Pin Chiang; Ling-Huey Chueh (Elsevier, 2021)
Background/purpose: Actinomycosis is sometimes associated with a radicular cyst (RC). This retrospective study evaluated the clinical and histopathological features of 6 RCs with actinomycosis (AM/RCs). Materials and methods: The demographic data and clinicopathological features of 6 AM/RCs were collected and analyzed. Results: The 6 AM/RCs were taken from 2 male and 4 female patients, and 3 were found in the maxilla and the other 3 in the mandible. The involved teeth included maxillary or mandibular incisors (2 cases) and maxillary or mandibular first and second molars (4 cases). The most common symptom was pain (5 cases) and the more frequent signs were sinus tract and pus discharge (4 cases). Microscopically, the actinomycotic colony presented as a mass with filamentous bacteria arranging in a sun-ray pattern at the periphery. The mean actinomycotic colony number was 7.7 ± 6.6 colonies per slide. Due to the severe inflammation in all 6 AM/RCs, the stratified squamous epithelial lining was completely abolished in 2 cases and partially destroyed in 4 cases with the residual epithelial lining varying from approximately 10%-50%. Conclusion: Our results indicate that pain is the most common symptom and sinus tract and pus discharge are the two frequent signs of our 6 AM/RCs. The stratified squamous epithelial lining was either completely abolished (2 cases) or partially destroyed (4 cases) in 6 AM/RCs. Thus, if the endodontically-treated tooth shows a recurrent sinus tract and poor response to repeated conventional root canal treatments, periradicular actinomycotic infection should be highly suspected.